2011
DOI: 10.1016/j.jcin.2011.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Implantation for Failing Surgical Aortic Bioprosthetic Valve

Abstract: TAV-in-SAV implantation is a safe and feasible treatment for high-risk patients with failing aortic bioprosthetic valves and should be considered as part of the armamentarium in the treatment of aortic bioprosthetic valve failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 23 publications
1
92
0
1
Order By: Relevance
“…The current study has demonstrated that ViV in stentless surgical bioprosthetic valve is feasible and safe with comparable clinical outcomes as in stented surgical bioprosthetic valve. Hemodynamics of ViV in the stentless group were superior with a larger effective orifice area Center series of 20 aortic valve patients with a 90% procedural success rate, 12 Our study has demonstrated comparable clinical outcomes of ViV in stentless group as compared to stented group. In the Global Valve-in-Valve Registry, high post-procedural gradients were common at 28%.…”
Section: Discussionsupporting
confidence: 51%
“…The current study has demonstrated that ViV in stentless surgical bioprosthetic valve is feasible and safe with comparable clinical outcomes as in stented surgical bioprosthetic valve. Hemodynamics of ViV in the stentless group were superior with a larger effective orifice area Center series of 20 aortic valve patients with a 90% procedural success rate, 12 Our study has demonstrated comparable clinical outcomes of ViV in stentless group as compared to stented group. In the Global Valve-in-Valve Registry, high post-procedural gradients were common at 28%.…”
Section: Discussionsupporting
confidence: 51%
“…Transcatheter aortic valve‐in‐valve (VIV) implantation in high‐risk patients with degenerative surgical bioprosthetic aortic valves is a novel application of transcatheter aortic valve replacement (TAVR) technology . Numerous case series, case reports and recently, the Global Valve‐in‐Valve registry have reported the safety and efficacy of transcatheter VIV procedure for degenerative bioprosthetic surgical aortic valves.…”
Section: Introductionmentioning
confidence: 99%
“…The frame of most bioprostheses can facilitate THV positioning. Smaller diameter valves (19 mm) will not facilitate the delivery of the currently available valves, but in patients with larger valves, a transcatheter valve-in-valve procedure may be a good option [4143]. A registry is currently being conducted of all valve-in-valve cases and is sponsored by Edwards Lifesciences.…”
Section: Future Directionsmentioning
confidence: 99%